Functional analysis of brain derived neurotrophic factor (BDNF) in Huntington’s disease - Zhou, Zhike (Aging (Albany NY), 2021)
The aim of this study is to determine the molecular functions of brain derived neurotrophic factor (BDNF) in Huntington’s disease (HD). A total of 1,675 differentially expressed genes (DEGs) were overlapped from HD versus control and BDNF-low versus high groups. Five co-expression modules were constructed using weight gene correlation network analysis, among which the blue and turquoise modules were most strongly correlated with HD and low BDNF. Functional enrichment analyses revealed DEGs in these modules significantly enriched in GABAergic synapse, phagosome, cyclic adenosine monophosphate (cAMP), mitogen-activated protein kinase (MAPK), renin-angiotensin system (Ras), Ras-associated protein-1 and retrograde endocannabinoid signaling pathways. The intersection pathways of BDNF, such as cAMP, MAPK and Ras signaling pathways, were identified in global regulatory network. Further performance evaluation of low BDNF accurately predicted HD occurrence according to the area under the curve of 82.4%. In aggregate, our findings highlighted the involvement of low BDNF expression in HD pathogenesis, potentially mediated by cAMP, MAPK and Ras signaling pathways.